Health or wealth? Analysing the impact of health outputs and outcomes vis-à-vis fiscal decentralisation in China - Chua, Jia Sheng (Nanyang Technological University, 2023)
Coinciding with the worldwide wave of fiscal decentralisation, China has sought to calibrate the amount of fiscal authority local governments possess through the Province-Managing-County (PMC) reform. Existing studies have proposed a positive causal linkage between fiscal decentralisation and socioeconomic indicators in China’s context, yet there remains a lack of research on healthcare indicators. This paper seeks to analyse how fiscal decentralisation affects health outputs and outcomes in China. We will utilise the PMC reform as an exogenous variation for establishing a quasi-natural experiment setting. A sequential approach is employed, where we will first prove the relationship between PMC and fiscal decentralisation through the vertical balance (VB) and the ratio of county expenditure to total provincial expenditure (RCE) indicators, before investigating the impacts of fiscal decentralisation on health outputs and outcomes. Extrapolating our empirical results, we argue that fiscal decentralisation has resulted in local officials sacrificing socioeconomic outcomes to pursue economic goals.